Numerical investigation on the effect of channelled and unchannelled screens on smoke contamination in atriums upper balconies with open upstand - Mutafi, M. (EDP Sciences, 2017)
Channel screens are used to restrict the smoke from spreading laterally under the first balcony. Effect of channel screens on smoke contamination in atrium upper balconies with the presence of balcony open upstand and 1m deep down stand at the fire compartment is investigated in this paper. Fire dynamic simulator (FDS6) which is a computational fluid dynamic (CFD) software was utilized to conduct the simulation. A comparison between the results of smoke contamination with the presence and omission of channeling screens showed that the height of smoke contamination in atrium upper balconies increased by 90 in case of no channel screens at the fire compartment are installed. A new correlation obtained from this work is able to predict the height of smoke contamination in atrium upper balconies with the presence of 1m deep down stand, balcony open upstand and no channel screens. © The authors, published by EDP Sciences, 2017.